Pengaruh Kompetensi Dan Kepemimpinan Terhadap Kinerja Pegawai Keuangan Badan Pusat Statistik Dengan Pemanfaatan Teknologi Informasi Sebagai Variabel Intervening - Ratih Ira Puspita; Mombang Sihita; Derriawan (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study entitled The Effect of Competence and Leadership on the Performance of Financial Officers at the Central Bureau of Statistics Using Information Technology as an Intervening Variable. The purpose of this study is to determine whether there is a significant influence between Competency and Leadership on Employee Performance with the Utilization of Information Technology as an Intervening Variable in Financial Officers of the Central Bureau of Statistics. The research used in this research is quantitative research. The quantitative research method is a type of research whose specifications are systematic, planned and structured from the start to the creation of a research design. Data management in this study will use smart PLS 3.2.9 software. Structural Equation Modeling (SEM) software is a method used to cover weaknesses in the regression method. While the sampling technique used is probability sampling, while the sampling method used is simple random sampling with a total sample of 250 people